Development of a Novel Immune Infiltration-Related ceRNA Network and Prognostic Model for Sarcoma - Shi, Deyao; Mu, Shidai; Pu, Feifei; Zhong, Binlong; Hu, Binwu; Liu, Jianxiang; He, Tongchuan; Zhang, Zhicai; Shao, Zengwu (Frontiers in Cell and Developmental Biology, 2021)
Due to the rarity and heterogeneity, it is challenging to explore and develop new therapeutic targets in patients with sarcoma. Recently, immune cells infiltration in the tumor microenvironment (TME) was widely studied, providing a novel potential approach for cancer treatment. The competing endogenous RNA (ceRNA) regulatory network has been reported as a critical molecular mechanism of tumor development. However, the role of ceRNA regulatory network in the TME of sarcoma remains unclear. In this study, gene expression data and clinical information were obtained from The Cancer Genome Atlas (TCGA) sarcoma datasets, and an immune infiltration related ceRNA network was constructed, which comprised 14 lncRNAs, 13 miRNAs and 23 mRNAs. Afterward, we constructed an immune infiltration related risk score model based on the expression of IRF1, MFNG, hsa-miR-940 and hsa-miR-378a-5p, presenting a promising performance in predicting the prognosis of patients with sarcoma.